Residential Attainment in the U.S. by Race, Ethnicity, and Family Structure: Do Married Households Have Better Outcomes? - Friedman, Samantha (Race and social problems, 2025)
Our study examines intra- and inter-group racial and ethnic differences in residential attainment by family structure. Though previous literature has found that significant racial and ethnic differences in residential attainment persist, little research examines those disparities by family structure within and between racial and ethnic groups. Existing research on family structure indicate that Black, single-mother families are particularly prone to experiencing residential segregation and discrimination in the housing market. These disadvantages in their residential attainment, compared to Black married couple families and other racial and ethnic groups by family structure, could have implications for the health and wealth accrual of Black, single-women-headed families. Using data from the 2019 American Housing Survey, we test hypotheses derived from the spatial assimilation and place stratification models through descriptive analyses and logistic regression models. We find that within racial and ethnic groups, married couple households tend to have better residential outcomes than single, women households. However, marriage does not prove to be an equalizer of residential outcomes across racial and ethnic groups. Controlling for relevant factors, Black and Hispanic married couple households have significantly inferior residential outcomes, relative to their white counterparts. In addition, these same residential disadvantages exist for Blacks and Hispanics, among single, women households. Our results suggest that while marriage is beneficial in terms of improved residential outcomes within racial and ethnic groups, structural forces of discrimination continue to disadvantage people of color in their residential attainment, regardless of their marital status.